Attempts of Modelling Forest Tree Volume and Biomass in Sri Lanka - Subasinghe, S. M. C. U. P. (Indian Forester, 2016)
Modelling forest tree volumehas a long history due to its importance in forest management decision making. However, tree biomass prediction become more popular recently because it has a strong relationship with carbon sequestration. Over the years, numerous attempts were made to construct allometric models in predicting tree volume and biomass in Sri Lanka for different forest species. Volume and biomass estimation in forest trees in Sri Lanka can be divided into four main types, i.e., (i) use of specific models built for the target species, (ii) use of models originally built for different tree species from the target once, (iii) use of common/universal conversions and (iv) use of remote sensing related studies. The first three types, however, became more common because mainly remote sensing studies do not facilitate the biomass estimation at the tree level. Details of tree volume and biomass prediction models constructed for Eucalyptus grandis, E. torelliana, E. microcorys, Tectona grandis, Pinus caribaea, Khaya senegalensis and Alstonia macrophylla are discussed in this paper. Moreover, it discusses the result of a study conducted in a wet zone natural forest to predict species-specific individual tree biomass using diameter as the only explanatory variable. Finally it elaborates the issues faced in developing allometric equations in Sri Lanka.